Shared Learning - Adler, Paul S. (Management Science, 1990)
Total productivity learning curve results are reported for several departments of an electronic equipment manufacturer with plants in the U.S., Europe and Asia. These results were used to focus qualitative field investigations into the behavioral and cognitive determinants of considerable diversity across departments in learning curve parameters. The field investigation suggested that three forms of shared learning are critical to manufacturing productivity improvement: (1) sharing across the Development/Manufacturing interface, (2) sharing between the primary location and plants that started up later, and (3) the ongoing sharing among plants after start-up. Innovations in each of these three processes are identified and mapped onto Daft and Lengel's information uncertainty/equivocality matrix. Implications for the role of manufacturing engineering are identified.